2016
DOI: 10.3126/njh.v13i2.15560
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Valvular Involvement in Rheumatic Heart Disease patients taking Benzathine Penicillin at Shahid Gangalal National Heart Centre, Kathmandu, Nepal

Abstract: Background and Aims: Acute rheumatic fever and rheumatic heart disease constitute an important public health problem in the developing countries. The disease results from an abnormal autoimmune response to a group A streptococcal infection in a susceptible host. We aim to describe the pattern of valvular involvement in patients taking Injection Benzathine Penicillin.Methods: All the patients, who were taking injection Benzathine penicillin during 15th April to 14th July, 2013 at our Centre, were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…2 In the present study Pure Mitral Stenosis (64.57%) was the most common lesion followed by pure Aortic Stenosis (8.86%), pure Mitral regurgitation (7.14%), pure Aortic Regurgitation (1.43%). These results were in accordance with the study done by Rabi Malla et al which showed MS as the most common valvular lesion, 13 However CN Manjunath 14 stated that MR was much more common than MS in the paediatric age group (<19 years) whereas in adults >20 years, MS was twice as common as MR. CN Manjunath also reported Rheumatic connection created the leading cause of valvular damage followed narrowly by myxomatous or mitral valve prolapse, comparable to the surgical series of Olson 15 (31% and 38% respectively) and Duren 16 (40% and 33% respectively).…”
Section: Discussionsupporting
confidence: 91%
“…2 In the present study Pure Mitral Stenosis (64.57%) was the most common lesion followed by pure Aortic Stenosis (8.86%), pure Mitral regurgitation (7.14%), pure Aortic Regurgitation (1.43%). These results were in accordance with the study done by Rabi Malla et al which showed MS as the most common valvular lesion, 13 However CN Manjunath 14 stated that MR was much more common than MS in the paediatric age group (<19 years) whereas in adults >20 years, MS was twice as common as MR. CN Manjunath also reported Rheumatic connection created the leading cause of valvular damage followed narrowly by myxomatous or mitral valve prolapse, comparable to the surgical series of Olson 15 (31% and 38% respectively) and Duren 16 (40% and 33% respectively).…”
Section: Discussionsupporting
confidence: 91%
“…Mitral valve disease was more common in female whereas aortic valve disease was more common in male. 13 In another study done by Rayamajhi A et al, mitral valve was the most commonly affected valve (82%). 14 In our study, isolated mitral valve was affected more (46.05%) than isolated aortic valve (1.9%) which was statistically significant in female patients with p value 0.013.…”
Section: Affected Valve and Valvular Lesionmentioning
confidence: 99%
“…The course of RHD is more rapid than in degenerative disease and predisposes to cardiac failure, secondary endocarditis, atrial fibrillation and stroke [46]. Most patients with RHD have mixed mitral valve stenosis and regurgitation [47]. Aortic regurgitation is seen in less than 50% of the patients and it is found almost always in combination with mitral valve disease; aortic stenosis is rare [48].…”
Section: Discussionmentioning
confidence: 99%